Unseen Threats: The Long‐term Impact of PET‐Microplastics on Development of Male Reproductive Over a Lifetime - Seungjin Jeong; GyuDae Lee; Surye Park; Myeongjoo Son; Seungjun Lee; Bomi Ryu (Advanced Science, 2025)
Abstract The physical abrasion of plastics from simple everyday entered the food chain, with associated risks recently emphasized. Although many studies have reported the adverse effects of microplastics (MPs) on human, the reproductive implications of continuous exposure to physically abraded polyethylene terephthalate (PET)‐MPs remain unexplored. Ingestion of physically abraded PET‐MPs (size range: 50–100 µm) in mice from 5 to 34 weeks of age at an annual intake relevant dose of MPs (5 mg week−1) significantly impaired male reproductive function. Reductions in seminiferous tubule diameter and epithelial height are observed (p < 0.0001), with 32.2% decrease in Leydig cells and 24.3% reduction in testosterone levels (p < 0.05). The epididymis shows marked deterioration in all regions, with total sperm concentration significantly reduce from 17.0 × 10⁶ to 5.3 × 10⁶ (p < 0.01) and decrease motility. Transcriptome analysis demonstrates downregulation of genes related with gonadotropin‐releasing hormone secretion, testosterone biosynthesis, and Meiosin gene, which is for crucial spermatogenesis. Continuous ingestion of physically abraded PET‐MPs from plastic bottles adversely affected testicular and epididymal functions, leading to hormonal imbalances and abnormal sperm production. These findings raise concerns about the impact of commonly used plastics on male reproductive development, highlighting potential risks for future generations.